Antioxidant Property of the Egyptian Propolis Extract Versus Aluminum Silicate Intoxication on a Rat’s Lung: Histopathological Studies - Ali H. Abu Almaaty; Yasmin M. Abd El-Aziz; Nahed A. Omar; Ahmed M. Abdeen; Hala Afifi; Tarek S. Ibrahim; Sameh S. Elhady; Amgad I. M. Khedr (Molecules, 2020)
In this study, we evaluated the inflammatory responses induced by aluminum silicate (AS) cytotoxicity in rat lungs. The prophylactic effect of propolis extract was evaluated in 60 adult male albino rats. The rats were divided into six groups: (1) a normal, healthy control group; (2) a normal group fed with 200 mL of propolis extract/Kg; (3) a low-dose positive control group injected with 5 mg/kg of AS; (4) a treated group given propolis and a low dose of AS; (5) a high-dose positive control group injected with 20 mg/kg of AS; and (6) a treated group given propolis with a high-dose of AS. At the end of the two-month experiment, the rats’ lungs were removed. For each pair of lungs, one portion was subjected to biochemical analysis and the other underwent hematoxylin and eosin (H&E) staining in order to study its histology. The rats that received AS doses displayed significant disorders in their antioxidant contents as well as in their enzymatic activities and their histopathological structures revealed severe damage to their lung tissues. Upon the rats being treated with propolis, the enzymatic and antioxidant contents improved and partial improvements in the lung structures appeared, including minimized congestion, a reduced hemorrhage of blood vessels and preserved bronchioles, alveolar ducts, and alveoli. The prophylactic effectiveness of propolis extract on the cytotoxicity of AS, owing to the antioxidant properties of propolis, were studied.